2010
DOI: 10.1902/jop.2009.090285
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Photodynamic Therapy for Periodontitis: A Systematic Review and Meta‐Analysis

Abstract: PDT as an independent treatment or as an adjunct to SRP was not superior to control treatment of SRP. Therefore, the routine use of PDT for clinical management of periodontitis cannot be recommended. Well-designed clinical trials are needed for proper evaluation of this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
0
20

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 29 publications
3
107
0
20
Order By: Relevance
“…The majority of reports indicate that PDT only results in decreasing the inflammation severity and there is insufficient evidence in relation to the effect of PDT on periodontitis. [35][36][37] Shibli et al 38 showed the effect of PDT on the pathogens within periodontal pockets. Meisel and Kocher 20 showed that the use of photosensitizing dyes and their activation with laser beams might result in the destruction of pathogens responsible for periodontal diseases and peri-implantitis.…”
Section: Effectiveness Of Photodynamic Therapy In Treatment Of Peri-imentioning
confidence: 99%
“…The majority of reports indicate that PDT only results in decreasing the inflammation severity and there is insufficient evidence in relation to the effect of PDT on periodontitis. [35][36][37] Shibli et al 38 showed the effect of PDT on the pathogens within periodontal pockets. Meisel and Kocher 20 showed that the use of photosensitizing dyes and their activation with laser beams might result in the destruction of pathogens responsible for periodontal diseases and peri-implantitis.…”
Section: Effectiveness Of Photodynamic Therapy In Treatment Of Peri-imentioning
confidence: 99%
“…30 Fotodinamik tedavi, cerrahi olmayan tedaviyle birlikte kullanıldığında ataçman seviyesinde tutarlı bir artış ve sondlama derinliğinde azalma tespit edildiği bildirilmiştir. 11,31,32 Endodonti Alanında FDT Endodontik tedavi kök kanal sistemi içindeki bakterilerin mekanik temizleme ve kimyasal yıkama protokolü ile ortadan kaldırılması için yapılan girişim-lerdir. Kök kanal sisteminin kök dallanmaları, lateral kanallar ve isthmuslarla ortaya çıkan anatomik karmaşıklık bakterilerin tamamen ortadan kaldırılmasını imkansız hale getirir.…”
Section: Periodontoloji Alanında Fdtunclassified
“…Despite this, the researchers warn of the need for more studies to prove these results. Azarpazhooh et al 35 published a systematic review and meta-analysis where articles were analyzed for the therapy of chronic and aggressive periodontitis. The PDT as independent or associated with the treatment was not exceeding SRP only.…”
Section: Photodynamic Therapymentioning
confidence: 99%